The Impact of Outward FDI in Central and Eastern Europe on Employment in the EU-15 Countries - Martin Falk; Yvonne Wolfmayr (FIW - Research Centre International Economics, 2008)
This paper has examined the home market effects of outward FDI into the CEE region based on the AMADEUS firm-level database. In particular, we investigated the substitution possibilities between foreign affiliate employment and parent company employment by distinguishing between manufacturing and non-manufacturing between the period 2000 and 2004. Despite fears of job losses in the home market due to outward FDI into the countries of central and Eastern Europe we find only limited evidence for the substitution of jobs between the parent companies in the EU15 and their affiliates in the CEEC. In particular we find that substitution possibilities are higher between employment in affiliates in high-wage countries and in the parent company than that of affiliate employment in the CEE region and parent company employment.
Keywords: 330; Foreign Direct Investment